Extraction of fixed oils from Sacha inchi (Plukenetia volubilis) seeds via ohmic heating: optimization and comparative study - Hamzah, Muhammad Hazwan; Jamaludin, Nur Fatihah; Aili Hamzah, Adila Fazliyana; Mohd Nor, Mohd Zuhair; Md Ali, Abd Halim; Mohd Ali, Maimunah; Che Man, Hasfalina (Springer, 2026)
Sacha inchi (Plukenetia volubilis) is a nutrient-rich oilseed valued for its high content of polyunsaturated fatty acids, particularly omega-3 and linoleic acid. Conventional extraction techniques such as steam distillation (SD) and hydro distillation (HD) are limited by low yields and high energy demands, reducing both efficiency and sustainability. This study evaluates ohmic-heated extraction (OHE), an electrically driven green technology, as an alternative method for oil recovery from sacha inchi seeds. Response surface methodology (RSM) was employed to optimize key parameters: reaction time, voltage, and solvent-to-solid ratio for maximizing oil yield. OHE performance was compared with SD and HD based on oil yield, energy efficiency, and physicochemical, antimicrobial, and morphological properties. The optimal OHE conditions were determined to be 70 V, 30 min, and a solvent-to-solid ratio of 7.06:1, resulting in a yield of 23.16%, significantly higher than that obtained by HD (10.6%) and SD (0.04%). Under these conditions, OHE produced a substantially higher oil efficiency of 225.89 mL/kWh with energy consumption of only 0.141 kWh, representing up to 91.21% savings compared with SD and HD. The oil obtained through OHE exhibited a light-yellow color and a refractive index of 1.48, comparable to conventionally extracted oils, although its specific gravity was slightly lower. Gas chromatography–mass spectrometry (GC–MS) analysis identified 17 chemical constituents, with linoleic acid methyl ester, hexadecanoic acid methyl ester, and methyl stearate as the dominant components across all extraction methods, reflecting the characteristic fatty acid composition of sacha inchi oil. Scanning electron microscopy further revealed pronounced structural disruption of seed tissues, indicative of enhanced cell wall breakdown and oil release. Overall, OHE demonstrates high efficiency, significant energy savings, and the ability to produce high-quality sacha inchi oil, highlighting its potential for sustainable applications in the food and cosmetic industries.